2018
DOI: 10.1016/j.beproc.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

To free, or not to free: Social reinforcement effects in the social release paradigm with rats

Abstract: The present research measured social reinforcement in rats, using a social-release procedure in which lever presses permitted 10-s access to a familiar social partner. The work requirements for reinforcement increased systematically according to progressive-ratio (PR) schedules. Social and food reinforcement value were compared across blocks of sessions (Experiment 1) and concurrently within the same sessions (Experiment 2). To assess motivational effects, response and reinforcer rates for both reinforcer type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 47 publications
6
37
0
Order By: Relevance
“…In that procedure, free rats that had learned to open the door to a restraint tube containing a trapped rat failed to extinguish responding when responding no longer provided access to the tube but did provide proximity to the trapped rat. This result can be explained in terms of sociality, but not the reinforcing properties of tube entry since tube entry was denied (also see Hiura et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In that procedure, free rats that had learned to open the door to a restraint tube containing a trapped rat failed to extinguish responding when responding no longer provided access to the tube but did provide proximity to the trapped rat. This result can be explained in terms of sociality, but not the reinforcing properties of tube entry since tube entry was denied (also see Hiura et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Hachiga et al (2018) interpreted these results as consistent with Silberberg et al's (2014) sociality premise. Hiura et al (2018) expanded on the results shown by Silberberg et al (2014) by arranging multiple trials in a session, presenting phases of acquisition and extinction, and varying postsession social restriction. Unlike Silberberg et al, they were able to show that free-rat behavior can come under the functional control of release of a restrained rat.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that social stimuli can function as contextual cues during extinction and a change in the extinction context characterized by social stimuli may produce renewal of operant responding. However, the above conclusion is based on the assertion that the presence of the second rat during extinction functioned as a contextual stimulus, but it is possible that the second rat may have served as a source of social reinforcement (Angermeier, 1960;Evans et al, 1994;Hiura, Tan, & Hackenberg, 2018). If the second rat served as a source of social reinforcement, then removal of this rat during test may have produced resurgence of responding rather than renewal.…”
Section: Discussionmentioning
confidence: 99%
“…If the presence of the social stimulus rat was a source of social reinforcement, then its removal in the test session may have produced resurgence of lever press responding instead of renewal. In fact, there is evidence that rats will respond for access to another rat (Calcagnetti & Schechter, 1992;Evans et al, 1994;Hiura et al, 2018;Humphreys & Einon, 1981), which suggests that social interaction can be used as a reinforcer. In addition, limited access to another rat through a screen may also be a source of social reinforcement (Angermeier, 1960;Peartree et al, 2012).…”
Section: Discussionmentioning
confidence: 99%